RHODIOLA ROSEA: STATUS OF RESEARCH AND POSSIBILITIES FOR COSMECEUTICAL AND DERMATOLOGICAL DRUGS PRODUCTION - E. F. Stepanova; B. Shirzad; S. B. Evseeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Rhodiola rosea is one of the most popular adaptogene agents. Apart from adaptogene, it has the whole range of other pharmaceutical properties: antioxidant, nootropic, antidepressant, immunomodulatory, and other. Russian industry manufactures liquid extract of Rhodiola rosea, as well as food BAS based on the Rhodiola rosea, but there are no dosage forms for external use.The purpose of this work is to analyze scientific information about general characteristics of the pharmacological activity and possible use of Rhodiola rosea in external drugs and cosmetics.Methods. The following resources were used for general characteristic of Rhodiola rosea, its pharmacological properties, particularly the usage of Rhodiola rosea in medical and cosmetic practices, as well prospects of its external use: eLIBRARY, PubMed, Cyberleninca, ResearchGate, information from manufacturers and dealers web-pages.Results. Rhodiola drugs are considered prospective agents for depressions therapy, Parkinson disease treatment, memory, attention defects, for arrhythmia prevention, stamina increase, and stress level decrease in sport and space medicine, for acceptability and efficiency improvement of chemo- and radiotherapy, as immunostimulatory agent. Nowadays in the Russian Federation Rhodiola rosea liquid extract is used as a tonic agent and is prescribed for over-fatigue in healthy persons, and for the sick, weakened as the result of a long-term treatment. Literature has sufficient amount of data about possible effect of biologically active substances of Rhodiola rosea at external use: antioxidant and antimicrobial, bleaching, UV-protective, metabolism stimulating.Conclusion. Thus, the data obtained give evidence about the prospect of Rhodiola use in cosmeceutics and prove the experience of its traditional use for withering and fat skin treatment, as well as acne.